The Role of Digital Marketing in Trade Development - Ilkhomovna, Usmonova Dilfuza; Shokhrukhovich, Usmanov Shakhzod (Research Parks Publishing LLC, 2023)
In this article, digital marketing strategy, development of network business, comprehensive approach to advertising, increasing sales volume, improving the company's reputation in the market, changing the location, changing the brand image, and solving certain business problems were considered.